Egypt in the era of Twelfth Dynasty (1991 - 1786 BC) - أ.م.د. ميثاق موسى عيسى; أ.م.د. فارس عجيل جاسم (Thi Qar Arts Journal, 2021)
This research revolves around the study of the internal conditions in ancient Egypt during the era of the Twelfth Dynasty, as Egypt witnessed the peak of its glory and prosperity after a long era of chaos and decline that extended from the end of the Sixth Dynasty to the end of the Tenth Dynasty, which is known as (the era of the first transition) an era in which the country lived A state of chaos and dispersion, and was characterized by the loose control of matters, and the king became powerless, and rampant dissolution and social disintegration, but with the assumption of the eleventh dynasty rule, Egypt began to recover and return to what it was in the era of the Old Kingdom of glory, and then reached the peak of its prosperity And its violence in the era of the Twelfth Dynasty. The kings of the Twelfth Dynasty carried out extensive reforms that included all political, administrative, economic, construction, art and literature fields